N-Heterocyclic carbene transition metal complexes in light emitting devices. (8th February 2018) - Elie, M.; Renaud, J.-L.; Gaillard, S.
Graphical abstract: In this minireview, a state of the art of the NHC transition metal complexes applied in two different modern technologies for lightening applications, namely Organic Light Emitting Diodes (OLEDs) and Light-Emitting Electrochemical Cells (LECs), is presented. In each technology, the different transition metal centres studied are described and the advantages brought by the NHC ligands in terms of electronic and steric properties is discussed. Devices obtained with these complexes are also presented and the stability and their efficiencies are also highlighted. Abstract: In this minireview, a state of the art of the NHC transition metal complexes applied in two different modern technologies for lightening applications, namely Organic Light Emitting Diodes (OLEDs) and Light-Emitting Electrochemical Cells (LECs), is presented. In each technology, the different transition metal centres studied are described and the advantages brought by the NHC ligands in terms of electronic and steric properties is discussed. Devices obtained with these complexes are also presented and the stability and their efficiencies are also highlighted.